A Techno-Philosophical Perspective on How Acceleration Becomes Autopoietic: Simplification as a Function of Technology. - Yu-cheng Liu (Techné: Research in Philosophy & Technology, 2019)
This study examines mainly two subjects: "Why do we accelerate?" and "How does acceleration become autopoietic?" The answers to these questions may be derived from technical, social, or psychological approaches. However, they provide only an incomplete picture if a perspective from the philosophy of technology is not considered alongside. In addition to offering different viewpoints on the essence of technology, technics, or technē, this study will focus on the notion of distance as a key to answering the above questions. Conventionally, people usually understand that technology distances humans from nature. However, what does that mean? First of all, the idea of "nature" considered in this research refers to a distinction of non-nature/ nature. A distinction implies a distance between both sides. Technology belongs to the side of non-nature, and creates a distance with the other side. The distance is getting enlarged when humans depend heavily on technology to reconnect humans to nature. In shortening or overcoming the distance, acceleration becomes autopoietic and leads to a paradox that can be unfolded only through accelerating more. In this study, technology is considered as a system functioning as simplification to create and to overcome alternately a distance with its environment, including nature. Through which technology not only acquires a tendency of acceleration, but also self-produces it. The development of writing tools from knots to tactile technology is investigated to provide a better understanding of the phenomenon of acceleration and its impact on humans and the world. In the end, it may be possible to think of a general theory of how acceleration becomes autopoietic.